Epidemiological and Clinical Features among COVID-19-positive Children in Eastern Uttar Pradesh (India): An Observational Study - Priyanka Singh; Suresh N Singh; Kuldeep Singh; Ajeet K Yadav; Anita Mehta; Vijay K Singh; Bhoopendra Sharma (Pediatric Infectious Disease)
Aim and background: The COVID-19 pandemic has been studied extensively in the adult population; however, information regarding epidemiological and clinical characteristics in pediatric patients is meager. The study presented in this research article aims to analyze some clinical features of COVID-19-positive children in eastern Uttar Pradesh, India. Materials and methods: An observational study was carried out involving 97 children admitted at BRD Medical College, Gorakhpur, Uttar Pradesh, India. The basic parameters involved in the study included age, gender, presence and number of symptoms, oxygen saturation levels at the time of admission, and geographic origin of the patients. Results: The study revealed that a considerable proportion of pediatric patients were asymptomatic (30.93%). Cases reported from rural populations were higher (54.64%) compared to urban regions (45.36%) of the study area. The majority of children (71.13%) maintained oxygen saturation levels above 95% at the time of admission, suggesting mild respiratory involvement. Conclusion: The study highlighted the varied clinical presentations of COVID-19 in children, necessitating targeted public health measures and surveillance across different geographical settings in eastern Uttar Pradesh.